Combination of White Blood Cell Count at Presentation With Molecular Response at 3 Months Better Predicts Deep Molecular Responses to Imatinib in Newly Diagnosed Chronic-Phase Chronic Myeloid Leukemia Patients. Issue 2 (January 2016) - Qin, Ya-Zhen; Jiang, Qian; Jiang, Hao; Lai, Yue-Yun; Zhu, Hong-Hu; Liu, Yan-Rong; Jiang, Bin; Huang, Xiao-Jun
Abstract : Abstract: The aim of this study was to evaluate the impact of white blood cell (WBC) counts at presentation on the achievement of deep molecular response. A total of 362 newly diagnosed chronic-phase chronic myeloid leukemia patients (CML-CP) receiving 400 mg/day imatinib were serially monitored for a median of 36 months (range 6–115). Patients showing an optimal response at 3, 6, and 12 months as defined by the 2013 European LeukemiaNet recommendations had significantly lower WBC counts at presentation than those showing nonoptimal responses (all P  < 0 .0001). Among the cutoff values with a similar Youden index, 150 × 10E9/L (abbreviated WBC > 150) was selected to identify the greatest amount of patients with the potential to achieve a sustained molecular response of 4.5 (MR4.5). Regardless of whether the Sokal risk score was included, the BCR-ABL IS value at 3 months, WBC counts at presentation, hemoglobin levels, and sex were the common independent predictors for an MR4.5, with the former 2 presenting the highest hazard risk. Low Sokal risk scores did not independently predict the achievement of an MR4.5. Patients with concurrent WBC > 150 and BCR-ABL IS ≤ 10% had a similar incidence of 4-year MR4.5 compared with patients with concurrent WBC ≤ 150 and BCR-ABL IS > 10% and concurrent WBC > 150 and BCR-ABL IS > 10% (13.5% vs 13.2% vs 8.8%, P  = 0.47), and all of these values were significantly lower than the values for patients with concurrent WBC ≤ 150 and BCR-ABL IS ≤ 10% (55.0%, all P  < 0.0001). Patients with concurrent WBC ≤ 150 and BCR-ABL IS ≤ 10% had better 4-year event-free survival rates, progression-free survival rates, and overall survival rates compared with patients with WBC > 150 or BCR-ABL IS > 10%. The combination of WBC count at presentation and BCR-ABL IS at 3 months provides improved predictions of deep molecular response in imatinib-treated CML-CP patients. Therefore, the WBC count at presentation might be used to differentiate patients at the beginning of imatinib treatment.